2019
DOI: 10.21873/anticanres.13145
|View full text |Cite
|
Sign up to set email alerts
|

The Role of KRAS in Endometrial Cancer: A Mini-Review

Abstract: Endometrial cancer (EC) is the most common cancer of the female genital tract, resulting annually in 76,000 related deaths worldwide. EC originates either from oestrogen-related proliferative endometrium (type I, endometrioid), or from atrophic endometrium (type II, non-endometrioid). Each type of EC is characterized by different molecular profile alterations. The Kirsten rat sarcoma viral oncogene homolog (KRAS) gene encodes a signalling protein which moderates response to various extracellular signals via do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 33 publications
2
55
1
Order By: Relevance
“…Sideris et al reported that a consensus on the exact way that KRAS overall affects EC prognosis has yet to be achieved [30]. In the present study, no signi cant correlation between KRAS mutation and OS was observed, so the prognostic signi cance of KRAS mutation remains controversial.…”
Section: Discussioncontrasting
confidence: 65%
“…Sideris et al reported that a consensus on the exact way that KRAS overall affects EC prognosis has yet to be achieved [30]. In the present study, no signi cant correlation between KRAS mutation and OS was observed, so the prognostic signi cance of KRAS mutation remains controversial.…”
Section: Discussioncontrasting
confidence: 65%
“…Mutations of KRAS result in constitutive activation of mitogen-activated protein kinase, which subsequently activates various downstream targets, leading to expression of genes involved in cellular proliferation, differentiation, and survival (10,30,31). Activating KRAS mutations have been detected in many human malignancies, particularly in pancreatic, colorectal, and pulmonary carcinomas, but also in endometrial and endocervical adenocarcinomas (32)(33)(34)(35)(36). At the early stage of carcinogenesis, the precancerous cells require KRAS for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological changes in these genes can cause anomalistic transduction of signal pathways such as AKT‐/‐PI3K, NF‐κB, MARK, and Wnt‐/‐β‐catenin, or abnormal expression of P53 and P16 proteins, leading to uncontrolled cell proliferation and tumorigenesis. Given its extensive study in tumors and obvious therapeutic effect, the CRISPR‐Cas9 technology has been used in related research and treatment of endometrial cancer (summarized in Table ).…”
Section: Endometrial Cancer and Crispr‐cas9mentioning
confidence: 99%